Training and deployment of lay refugee/internally displaced persons to provide basic health services in camps: a systematic review - John E. Ehiri; Jayleen K.L. Gunn; Katherine E. Center; Ying Li; Mae Rouhani; Echezona E. Ezeanolue (Taylor & Francis Group, 2014)
Background: Training of lay refugees/internally displaced persons (IDPs) and deploying them to provide basic health services to other women, children, and families in camps is perceived to be associated with public health benefits. However, there is limited evidence to support this hypothesis. Objectives: To assess the effects of interventions to train and deploy lay refugees and/or IDPs for the provision of basic health service to other women, children, and families in camps. Methods: PubMed, Science and Social Science Citation Indices, PsycINFO, EMBASE, POPLINE, CINAHL, and reference lists of relevant articles were searched (from inception to June 30, 2014) with the aim of identifying studies that reported the effects of interventions that trained and deployed lay refugees and/or IDPs for the provision of basic health service to other women, children, and families in camps. Two investigators independently reviewed all titles and abstracts to identify potentially relevant articles. Discrepancies were resolved by repeated review, discussion, and consensus. Study quality assessment was undertaken using standard protocols. Results: Ten studies (five cross-sectional, four pre-post, and one post-test only) conducted in Africa (Guinea and Tanzania), Central America (Belize), and Asia (Myanmar) were included. The studies demonstrated some positive impact on population health associated with training and deployment of trained lay refugees/IDPs as health workers in camps. Reported effects included increased service coverage, increased knowledge about disease symptoms and prevention, increased adoption of improved treatment seeking and protective behaviors, increased uptake of services, and improved access to reproductive health information. One study, which assessed the effect of peer refugee health education on sexual and reproductive health, did not demonstrate a marked reduction in unintended pregnancies among refugee/IDP women. Conclusion: Although available evidence suggests a positive impact of training and deployment of lay refugees/IDPs as health workers in camps, existing body of evidence is weak, and calls for a re-examination of current practices. Interventions that promote training and deployment of lay refugees/IDPs as health workers in camps should include strong evaluation components in order to facilitate assessment of effects on population health.